Taking Brief Strategic Family Therapy from Bench to Trench: Evidence Generation Across Translational Phases. Issue 3 (14th July 2016) - Horigian, Viviana E.; Anderson, Austen R.; Szapocznik, José
Abstract : In this article, we review the research evidence generated over 40 years on Brief Strategic Family Therapy illustrating the NIH stages of intervention development and highlighting the translational process. Basic research (Stage 0) led to the discovery of the characteristics of the population and the nature of the problems that needed to be addressed. This step informed the selection of an intervention model that addressed the problems presented by the population, but in a fashion that was congruent with the population's culture, defined in terms of its value orientations. From this basic research, an intervention that integrated structural and strategic elements was selected and refined through testing (Stage I). The second stage of translation (Stage II) included efficacy trials of a specialized engagement module that responded to challenges to the provision of services. It also included several other efficacy trials that documented the effects of the intervention, mostly in research settings or with research therapists. Stages III/IV in the translational process led to the testing of the effectiveness of the intervention in real‐world settings with community therapists and some oversight from the developer. This work revealed that an implementation/organizational intervention was required to achieve fidelity and sustainability of the intervention in real‐world settings. The work is currently in Stage V in which new model development led to an implementation intervention that can ensure fidelity and sustainability. Future research will evaluate the effectiveness of the current implementation model in increasing adoption, fidelity, and long‐term sustainability in real‐world settings.